Mendemarkasi Kebenaran dalam Media Digital: Kerangka Popperian untuk Menanggulangi Berita Palsu - Wijaksono, Dimas; Azwar; Kuswanti, Ana; Kusumajanti (KOMUNIKA, 2026)
The rapid spread of fake news in the digital media era has generated serious problems, including declining public trust in the media, social polarization, and distortion of democratic processes. This condition calls for a conceptual approach that can assist the public and media practitioners in distinguishing credible information from misinformation. This study aims to analyze the contribution of Karl R. Popper’s falsification theory in understanding and addressing the phenomenon of fake news within the contemporary media ecosystem. The research employed a library research method, using documentation techniques to collect data from books, academic journals, and relevant scholarly publications. The data were analyzed through systematic and thematic content analysis. Claims that cannot be empirically tested tend to have a high potential to be misinformation. The study also demonstrates that Popperian principles can be integrated with digital technologies, such as artificial intelligence and machine learning, in evidence-based hoax detection systems. In conclusion, Karl Popper’s falsification theory makes a significant contribution to strengthening media literacy, communication ethics, and public resilience against fake news. This framework is not only philosophically relevant but also practically applicable in journalistic practices and the development of information verification technologies in the digital era